(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
In this work we seek from the concept of sovereignty to establish its causes and effects, among which are social, economic, moral and political. In the complex war against corruption there are some combatants, such as the rule of law, represented by the country’s laws (Administrative Improbity Law, Public Administration Contracts and Law, Anticorruption Law and Clean Registry Act) and international conventions (Inter-American Convention against Corruption – OAS/1996, United Nations Convention against Corruption – UN/2003, Convention on Combating Bribery of Foreign Public Officials in International Business Transactions – OECD/1997) and constitutional anticorruption, such as the Public Prosecutor’s Office, Administrative Council for Economic Defense and the Federal Police. In power the ruler must be guided by an ethical conduct, always reflecting the popular will, in the face of the interests that he manages. The people granting sovereignty to a certain ruler, being a political-governmental directive in the Democratic State of Right, can not accept practices with deviations from purpose, nor rules that fit the politics of government and that lead to corruption, although by third parties. Anticorruption measures are necessary because they limit the arbitrary power of the ruler and are intended to satisfy the public interest. However, this is not efficient, and freedom of expression and a free press are indispensable, which only democratic regimes can foster. The fight against corruption must be diuturnal so that impunity does not facilitate the advance of corruption in the social sphere and thus we can have decent health and education, as well as the improvement of the human development index.